1996
DOI: 10.1016/s0022-5347(01)65682-9
|View full text |Cite
|
Sign up to set email alerts
|

Penile Length in the Flaccid and Erect States: Guidelines for Penile Augmentation

Abstract: Only men with a flaccid length of less than 4 cm., or a stretched or erect length of less than 7.5 cm. should be considered candidates for penile lengthening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
233
3
14

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(258 citation statements)
references
References 9 publications
8
233
3
14
Order By: Relevance
“…Wessell et al [11] reported that, although stretched penile length closely correlated with erect length, there was an average discrepancy of 0.5 cm between the two. Deveci et al [9] compared the stretched flaccid penile length before and after the IPP and found that penile prosthesis did not have a negative impact on the measurement of stretched flaccid penile length even though 72% of patients reported a decrease of penile length in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Wessell et al [11] reported that, although stretched penile length closely correlated with erect length, there was an average discrepancy of 0.5 cm between the two. Deveci et al [9] compared the stretched flaccid penile length before and after the IPP and found that penile prosthesis did not have a negative impact on the measurement of stretched flaccid penile length even though 72% of patients reported a decrease of penile length in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no standard technique for measuring penile size, there appears to be a consensus among researchers that penile length should be measured on the dorsum of the penis beginning from the pubopenile junction to the tip of the glans ( Figure 1). 5 This measurement applies to the flaccid, stretched and erect states. In addition, measurements of penile girth should be obtained from the middle of the penile shaft, in all three states.…”
Section: Penile Sizementioning
confidence: 99%
“…Furthermore, flaccid penile girth measurements were 9.75 cm for 11 The validity of self reported measurements needs to be considered when evaluating these data. Wessells et al 5 published their data regarding penile length and indications for penile augmentation. They examined penile lengths in 80 men with a mean age of 54 years.…”
Section: Penile Sizementioning
confidence: 99%
“…The mean erect penile length, according to the guidelines (13.3 cm), is closely correlated with the results (12.9 cm) obtained in White, Black, and Asian patients, indicating its applicability regardless of the race. [8][9][10] To the best of our knowledge, the inclusion of the erect penile length into the criteria for selection of surgical technique has not been reported yet. On the other hand, in severe deviations, there is even more significant penis shortening if the shortening procedures are used.…”
Section: Discussionmentioning
confidence: 99%